(untitled) (Ghana Journal of Science, Technology and Development, 2020)
Fish preservation methods including use of formalin and freezing are widely used to preserve fish specimen in the laboratory to maintain their freshness for future laboratory analysis. This present study aimed to investigate the effects of fixation and freezing on the morphometric characteristics of Nile tilapia, Oreochromis niloticus. Forty (40) samples of a single cohort of O. niloticus were obtained from the Tono reservoir in Navrongo, Ghana. Total length (TL) and body weight (W) of each fish were measured. Twenty (20) samples of O. niloticus were subjected to freezing at -4ÂºC whilst the remaining twenty (20) were fixed in 4% formaldehyde solution. The study lasted for thirteen (13) days during which the length and weight were determined repeatedly in a sequence during the storage period. Although there was no significant difference (p > 0.05) in the change of length and weight measured during the study, all samples showed some degree of shrinkage within the storage period. For samples preserved by freezing, there was a 5.62 % and 19.61 % reduction in length and weight respectively, while those preserved in formalin reduced by 5.24% and 10.72% in length and weight respectively. For condition factor (k), there was no change at the end of the experiment for samples preserved by freezing but a marginal increase of 0.08% was realized for those preserved in formalin. Though shrinkage occurred in both samples preserved in formalin and freezing, the greatest shrinkage was recorded by those preserved by freezing.